THE EFFECT OF CONCENTRATION AND SOAKING LENGTH OF ALOE VERA GEL ON THE GROWTH OF ROBUSTA COFFEE (Coffea canephora) CUTTINGS - Rahmawati, Nurul Diah; Historiawati; Nurul Iftitah, Siti (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine the effect of concentration and soaking time of aloe vera gel on the growth of robusta coffee cuttings. The research was arranged in a Randomized Complete Group Design (RAKL) with a factorial experiment (4x2) consisting of two treatment factors and repeated three times as a block. The first factor is the concentration of aloe vera gel with levels of 0, 20, 40, and 60%. The second factor is the length of soaking with levels of 5 and 10 hours. The results were analyzed using variance analysis, treatments that had a significant effect were further tested with Orthogonal Polynomial for the first factor and interaction and the Least Significant Difference (LSD) test for the second factor. The results showed that 40% aloe vera gel concentration produced the highest root dry weight. The treatment of aloe vera soaking time for 5 hours produced the longest root length. The interaction between aloe vera gel concentration of 20% and soaking time for 5 hours produces the longest root length.